Brazilian monetary system domino through the universal design for learning - Stellfeld, Janaina Zanon Roberto; Jocoski, Juarês; Kuroki, Júlia Helena; Góes, Anderson Roges Teixeira; Agranionih, Neila Tonin (Revista Brasileira de Educação em Ciências e Educação Matemática, 2023)
This study presents a domino game of the Brazilian Monetary System developed based on the principles of Universal Design and Universal Design for Learning. The objective is to use the game as a pedagogical resource to mediate, interact, and intervene in the teaching of Mathematics content in classrooms. The game was implemented in a class of 28 students from the 3rd year of Elementary School in a public school in Araucária/PR, including children with special needs in Mathematics classes. The results showed that the game promoted inclusive lessons, facilitating content comprehension and encouraging social interaction. The game strategy demonstrated effectiveness in the cognitive, mathematical, and social development of the students, stimulating collaboration and meaningful learning. The use of accessible resources was crucial to ensure the inclusion of all students. This approach has the potential to contribute to a participatory, affective, and equitable education, offering lifelong opportunities for meaningful learning.